2009
DOI: 10.1063/1.3187905
|View full text |Cite
|
Sign up to set email alerts
|

The effect of off-axis neutral beam injection on sawtooth stability in ASDEX Upgrade and Mega-Ampere Spherical Tokamak

Abstract: Sawtooth behaviour has been investigated in plasmas heated with off-axis neutral beam injection (NBI) in ASDEX Upgrade [A. Herrmann and O. Gruber, Fusion Sci. Technol. 44, 569 (2003)] and the Mega-Ampere Spherical Tokamak (MAST) [A Sykes et al., Nucl. Fusion 41, 1423(2001]. Provided that the fast ions are well confined, the sawtooth period is found to decrease as the neutral beam is injected further off-axis. Drift kinetic modelling of such discharges qualitatively shows that the passing fast ions born outside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…This mechanism is described in detail in [9,10]. The effect of passing fast ions has been confirmed in NBI experiments in JET [11,12], ASDEX Upgrade [13] and MAST [14] and using He 3 minority ICRH in JET [15,16]. By employing He 3 minority heating schemes (which are envisaged for ITER ICRF heating), the resultant current drive is negligible [10,17].…”
Section: Introductionmentioning
confidence: 96%
“…This mechanism is described in detail in [9,10]. The effect of passing fast ions has been confirmed in NBI experiments in JET [11,12], ASDEX Upgrade [13] and MAST [14] and using He 3 minority ICRH in JET [15,16]. By employing He 3 minority heating schemes (which are envisaged for ITER ICRF heating), the resultant current drive is negligible [10,17].…”
Section: Introductionmentioning
confidence: 96%
“…[45], the outermost beam, with R tan =130 cm, provides substantial off-axis neutral beam current drive (NBCD). Note that off-axis NBCD has been observed in conventional aspect ratio tokamaks [50][51][52][53][54], as well as STs [55].…”
Section: : the Nstx-upgrade Facilitymentioning
confidence: 99%
“…The neutral beam current drive [50][51][52][53][54][55][62][63][64] is computed by the NUBEAM code [65]; 8000 to 16000 particles were typically used in these simulations, weighted toward the plasma core to reduce the Monte-Carlo noise on the central beam current drive (wghta=10 [65]). The beam-current shielding factor derived by Lin-Liu & Hinton [64] is used.…”
Section: Free-boundary Transp Simulationsmentioning
confidence: 99%
“…Off-axis NBI has been used to investigate sawtooth behavior in JET [8], MAST and ASDEX-U [9]. By drift kinetic modeling, they have found that the stability of n = 1 internal kink mode, which is thought to be related to sawtooth instability, is destabilized by the passing ions born outside the q = 1 rational surface due to the NBI.…”
Section: The Capability To Control Mhd Activitiesmentioning
confidence: 99%
“…Reasonable agreement between the measured and calculated (with D b ∼ 0-0.5 m 2 s −1 ) NBCD related physical quantities in all of the tokamak plasmas without magnetohydrodynamic (MHD) activities, except ELMs, have been published [1][2][3][4][5][6][7]. In JET [8], ASDEX-U and MAST [9], the experimental results showed that it is possible to control sawtooth by off-axis NBI with an off-axis peaked fast ion distribution.…”
Section: Introductionmentioning
confidence: 99%